Epoetin alfa in patients with advanced-stage Hodgkin's lymphoma: results of the randomized placebo-controlled GHSG HD15EPO trial - Engert, Andreas; Josting, Andreas; Haverkamp, Heinz; Villalobos Bollen, Matthias Americo; Lohri, Andreas; Sökler, Martin; Zijlstra, Josée; Sturm, Isrid; Topp, Max S.; Rank, Andreas; Zenz, Thorsten; Vogelhuber, Martin; et al. (Journal of clinical oncology, 2010)
Purpose: To determine whether epoetin alfa reduces anemia-related fatigue, improves other aspects of health-related patient-recorded outcomes (PROs), reduces the number of RBC transfusions, and has an impact on freedom from treatment failure (FFTF) and overall survival (OS) in patients with advanced-stage Hodgkin's lymphoma (HL). - Patients and Methods: The prospectively randomized HD15EPO study performed by the German Hodgkin Study Group investigated epoetin alfa administered at doses of 40,000 U weekly during and after chemotherapy (six to eight cycles of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone [BEACOPP]) in a double-blind, placebo-controlled setting. The study accrued 1,379 patients, of whom 1,328 were assessable for safety, 1,303 were assessable for clinical outcome, and 930 were assessable for PROs. - Results: PROs were not different in patients receiving placebo or epoetin alfa, both after the end of chemotherapy and 6 months thereafter. There was no difference between patients treated with epoetin alfa or placebo with respect to FFTF and OS. There were also no differences in the numbers of deaths, progressions, relapses, and thromboembolic events. The median number of RBC transfusions was reduced from four per patient in the placebo group to two per patient in the epoetin alfa group (P < .001), with 27.4% of patients needing no RBC transfusion in the placebo group compared with 36.7% of patients in the epoetin alfa group (P < .001). - Conclusion: Epoetin alfa administered at 40,000 U weekly parallel to BEACOPP chemotherapy was safe in patients with advanced-stage HL and reduced the number of RBC transfusions but had no impact on fatigue and other PRO domains.